The Role of Political Stability in Nine Arab Natural Resource-Abundant Countries (ANRAC) Toward Environmental Sustainability through CO2 Mitigation - Fatah, Omed Rafiq; Altaee, Hatem Hatef Abdulkadhim (International Journal of Energy Economics and Policy, 2024)
This study examines the intricate interplay of political stability, natural resource rent, industrialization, globalization, economic growth, and carbon emissions in nine Arab resource-abundant countries (ANRAC) from 1996 to 2019. Applying advanced statistical approaches, such as the Method of Moment Quantiles Regression (MMQREG) as a baseline estimation approach, along with the inclusion of PCSE, FGLS, and FMOLS, to enhance, to enhance the reliability and stability of the obtained results. The study results suggest that globalization, coupled with the interplay between political stability and economic growth, fosters advancements in environmental conditions and the pursuit of sustainable practices. In contrast, political stability, abundant natural resources, sustained economic expansion, and widespread industrialization are associated with increased CO2 emissions, posing detrimental effects on the environment. Notably, there seems to be a correlation between the concurrent improvement of political stability and economic growth and a reduction in CO2 emissions.